1987
DOI: 10.1111/j.1365-3040.1987.tb02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene stimulates the accumulation of ripening-related mRNAs in tomatoes

Abstract: Seven cDNA clones for ripening-related mRNAs were used as hybridization probes to study the regulation of gene expression during tomato {Lyeopersieon eseulentum Mill) ripening. The mRNAs corresponding to each clone were detected by Northern blotting and the sizes of the transcripts compared with the molecular weights of polypeptides identified previously by hybrid-release translation. Dot hybridization to poIy(A)-t-mRNA from leaves, roots, unripe and ripe tomatoes established that five of the clones encoded mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…This increase in ethylene appears to play a pivotal role in ripening by triggering the expression of several ripening-specific genes involved in many of the subsequent changes associated with the ripening process (Yang, 1985). A number of ripening-related mRNAs have been shown to accumulate in response to ethylene (Lincoln et al, 1987;Maunders et al, 1987). Similarly, we have shown that treatment with this hormone is able to induce the expression of BanU in green banana fruits.…”
Section: Discussionmentioning
confidence: 60%
“…This increase in ethylene appears to play a pivotal role in ripening by triggering the expression of several ripening-specific genes involved in many of the subsequent changes associated with the ripening process (Yang, 1985). A number of ripening-related mRNAs have been shown to accumulate in response to ethylene (Lincoln et al, 1987;Maunders et al, 1987). Similarly, we have shown that treatment with this hormone is able to induce the expression of BanU in green banana fruits.…”
Section: Discussionmentioning
confidence: 60%
“…The cloning of these two genes is now allowing a more precise analysis of the functions of ethylene during plant development. The most extensively studied of these is the role of ethylene in inducing and coordinating the changes in gene expression which occur during the ripening of climacteric fruit (Abeles, 1973;Christoffersen et a/., 1982;Davies and Grierson, 1989;Davies et a/., 1988Davies et a/., , 1990Grierson et a/., 1986a;Lincoln et a/., 1987;Maunders et a/., 1987;Yang and Hoffman, 1984). Recently, tomato plants in which the synthesis of the ethylene precursor ACC was almost completely inhibited by an ACC-synthase antisense transgene have been described (Oeller eta/., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression of many genes encoding enzymes that give rise to the ripe phenotype is known to be regulated by ethylene (Lincoln et al, 1987;Maunders et al, 1987;Zegzouti et al, 1999).…”
mentioning
confidence: 99%